(untitled) (Indian Journal of Animal Production and Management, 2026)
This study included a hatching experiment to investigate the effect of early feeding using different levels of gamma-aminobutyric acid (GABA) solution on hatchability and characteristics of hatched broiler chicks. Six hundred hatchable eggs from a single flock of Ross 308 broiler breeders, 46 weeks old, were used. The eggs, weighing 64 g each, had been stored for two days and were incubated in a setter at 99.8°F (37.8°C) and 60% relative humidity. The eggs were turned automatically once every hour. On day 18 of incubation, before transferring the eggs to the hatcher, they were candled in a sterile, dark room (egg transfer room) at 25°C and 55% relative humidity. Four hundred and eighty fertilized eggs were randomly divided into four treatments, with three replicates per treatment. In a treatment of 40 eggs per replicate, the eggs were incubated in the hatcher at 98.6°F (37°C) and 70% relative humidity until hatching. The treatments were distributed as follows: T1 (negative control): Hatching eggs without injection T2 (carrier control): Hatching eggs injected with 0.2 ml/egg of N.S. T3: Hatching eggs injected with 0.2 ml/egg of 10% gamma-aminobutyric acid solution. T4: Hatching eggs injected with 0.2 ml/egg of 15% gamma-aminobutyric acid solution. The hatching rates observed showed that the injection treatments T3 and T4 were significantly superior to the negative control and carrier treatments T1 and T2 in terms of embryonic mortality. The mortality rate was lower in T3 and T4 (0.83 and 1.12, respectively) compared to 2.50 for the control treatment T1. There was also a significant advantage (P ≤ 0.05) in both the overall hatching rate and the hatching rate of fertilized eggs for the injection treatments T3 and T4. These treatments significantly outperformed the negative control and carrier treatments T1 and T2, recording 96.66% and 94.76% for the overall hatching rate and 96.66% and 94.76% for the hatching rate of fertilized eggs, respectively, compared to 93.33% and 93.33% for the control and carrier treatments T1 and T2, respectively. In terms of hatchability and live pecking percentage, the third and fourth injection treatments (T3 and T4) significantly outperformed the other treatments, recording 95.83% and 92.83%, respectively, compared to 91.66% for the control treatment (T1). The same table shows no significant differences between the treatments in the percentage of dead pecking chicks. Regarding vital organs, a significant decrease in the percentage of residual yolk was observed in the injection treatments (T3 and T4) at 3.00% and 3.34%, compared to 3.76% for the control treatment (T1). No significant differences were found between the treatments in the percentages of heart, liver, pancreas, and spleen. Regarding immunoglobulin (Ig) characteristics, there was a significant improvement, with the third and fourth injection treatments (T3 and T4) outperforming the other treatments. These treatments recorded Ig levels of 45.33 and 45.33 mg/ dl, respectively, compared to 39.33 mg/dl for the control treatment (T1). The two treatments also recorded Ig levels of 1044.33 and 1048.33 mg/dL, respectively, compared to 1004.00 mg/dl for the control treatment (T1). Regarding vital organ measurements, an increase in the fetus’s ability to utilize residual yolk was observed. A significant decrease in the relative weight of residual yolk was noted in the early feeding treatments (T3 and T4), reaching 3.00% and 3.34%, respectively. Compared to the negative control and carrier treatments T1 and T2, which reached 3.76% and 3.62%, respectively, the same table shows no significant differences between the experimental treatments in the percentage weight of the heart, liver, spleen, and pancreas of the chicks at hatching. Regarding biochemical characteristics, a significant decrease was observed in the T3 and T4 injection treatments in both aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels, which were recorded at 141.46 and 142.36 U/L, respectively, compared to 180.33 U/L for the control treatment T1. For ALT, the T3 and T4 injection treatments recorded 3.22 and 3.31 U/L, respectively, compared to 3.86 U/L for the control treatment T1. No significant differences were observed between the treatments in the percentage of albumin and globulin, while a significant difference was observed (P ≤ 0.05) in the protein ratio, where the T3 injection treatment outperformed the control treatment and the rest of the experimental treatments, as T3 recorded 6.65 g/100 ml protein compared to 6.35 g/100 ml for the control treatment T1.